Chronic fatigue and headache in post-COVID-19 syndrome: a radiological and clinical evaluation - Almeida, Gonçalo G.; Alkan, Saide; Hoepner, Robert; Euler, André; Diem, Lara; Wagner, Franca (Frontiers in Neurology, 2025)
IntroductionThe coronavirus disease 2019 (COVID-19) pandemic has caused millions of infections and deaths globally. Post-COVID-19 syndrome, or long COVID is characterized by lingering symptoms such as chronic fatigue, headaches, and sleep disturbances. This study aimed to investigate the correlation between these symptoms and T2-hyperintense white matter lesions detected on magnetic resonance imaging (MRI) of the brain and spine in patients with post-COVID-19 syndrome.MethodsThis retrospective, single-center study analyzed a sample of 96 patients from Bern University Hospital in Switzerland who presented with suspected post-COVID-19 syndrome between 2020 and 2022. Patients completed self-report questionnaires evaluating fatigue, emotional wellbeing, and daytime sleepiness. Brain and spine MRIs were independently rated by 2 neuroradiologists for T2-hyperintense lesions. The correlation between these lesions and symptoms of fatigue and headache was assessed.ResultsThe cohort consisted predominantly of women (73%) with an average age of 46 years. Chronic fatigue (90%), sleep disorders (51%), and headache (57%) were the most prevalent symptoms. The fatigue questionnaires indicated high levels of fatigue. Brain MRI revealed T2-hyperintense lesions in 72% of patients, whereas spine MRI showed these lesions in only 16%. There was no statistically significant correlation between the presence of cerebral T2-hyperintense lesions and symptoms of fatigue (p = 0.815) or headaches (p = 0.178). Similarly, no significant correlation was found when considering numbers of pathological brain lesions (fatigue: p = 0.557; headaches: p = 0.820).ConclusionWhile T2-hyperintense lesions are common in patients with post-COVID-19 syndrome, their presence does not correlate significantly with symptoms of fatigue or headaches. These findings suggest that T2-hyperintense brain lesions may not be directly related to the subjective experience of these symptoms. Further research with larger sample sizes and adjustment for potential confounding factors is necessary to better understand the relationship between MRI findings and post-COVID-19 syndrome symptoms.